Formulation and evaluation of buccal film of Ivabradine hydrochloride for the treatment of stable angina pectoris - Lodhi, Mohasin (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Ivabradine hydrochloride is an anti-anginal drug with a biological half-life of about 2 h, and repeated daily administration is needed to maintain effective plasma level. Present investigation of buccal films of Ivabradine hydrochloride is an attempt to avoid the repeated administration and release of drug in more controlled fashion, thereby, to improve the bioavailability. MATERIALS AND METHODS: Buccal patches were fabricated by solvent casting technique and were evaluated for its physical properties like physical appearance, weight uniformity, thickness, swelling index, surface pH, mucoadhesive time, and folding endurance, in vitro and ex vivo release studies. RESULTS: A combination of hydroxypropyl methyl cellulose (HPMC) K15M and K100M with carbopol 940, PEG 6000 gave promising results. Further, the drug content of all the formulations was determined and was found to be uniform. All the formulations were subjected to in vitro release study using phosphate buffer pH 6.6. Patches exhibited drug release in the range of 90.36% ± 0.854 to 98.37% ± 0.589 at the end of six hrs. The best formulations (F2 and F5) containing the composition of HPMC K15-37.50 mg, carbopol-0.42 mg, PEG6000-16.87 mg, Aspertane-0.28 mg, Tween-0.0023 mg and HPMC K100-37.50 mg, carbopol-0.42 mg, PEG6000-16.87 mg, Aspertane-0.28 mg, Tween-0.0023 mg respectively exhibited in vitro drug release of 97.61% ± 0.589 and 98.37% ± 0.114 respectively. The results of ex vivo diffusion using goat cheek pouch revealed that the drug release rate was retarded up to seven hrs. Films prepared with permeation enhancer (Tween 80) showed faster drug release. Finally, stability studies were carried out by using human saliva for the optimized formulation (F2-F5). CONCLUSION: The present study indicated enormous potential of mucoadhesive buccal patches containing Ivabradine for systemic delivery with an added advantage of circumventing hepatic first pass metabolism. Further work is recommended to support its efficacy claims by long term pharmacokinetic and pharmacodynamic studies in human beings.